ASSESSMENT OF HEAVY METAL CONTAMINATION IN ANAMBRA RIVER, NIGERIA - AGBABIAKA, L.A; IBEMENUGA, K.N. (Nigerian Journal of Fisheries, 2020)
The concentration of heavy metals (Cd, Zn, Mn, Cu, and Pb) in water and sediment samples collected from five study stations along Anambra River was assessed for one month. The samples were obtained in plastic containers and carried to the laboratory for analysis of the selected heavy metals. The concentration of the various heavy metals in water and sediment samples were determined using an atomic spectrophotometer. Data obtained were analyzed using descriptive analysis to establish means significant difference in the concentration of heavy metals was evaluated using Analysis of variance (ANOVA). Heavy metals in water occurred in the order Zn>Pb>Cu>Cd while the trend in sediment was Zn>Mn>Pb>Cu>Cd. All the studied heavy metals except for manganese were observed in the water at all the stations. In water and sediment samples, zinc dominated the other heavy metals at all the study stations. The concentration of cadmium, manganese, and lead were above the WHO acceptable limits while the concentrations of zinc and copper were within the permissible limits. Thus, Anambra River is slightly polluted. The river, therefore, should be treated and monitored to prevent further contamination.